2017
DOI: 10.1136/tobaccocontrol-2017-053751
|View full text |Cite
|
Sign up to set email alerts
|

Second-hand smoke exposure in homes with children: assessment of airborne nicotine in the living room and children’s bedroom

Abstract: Homes with smokers present SHS in the living room and in the children's bedroom. Therefore, programmes focused on reducing children's SHS exposure are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…In this setting, the prevalence of exposure in our study was 26%. Furthermore, according to a recent study 8 , the level of exposure in this setting might be very high, with nicotine concentration levels similar to those found in public places before the implementation of the tobacco control laws. Therefore, SHS exposure at home might have an important public health impact.…”
Section: Discussionsupporting
confidence: 60%
“…In this setting, the prevalence of exposure in our study was 26%. Furthermore, according to a recent study 8 , the level of exposure in this setting might be very high, with nicotine concentration levels similar to those found in public places before the implementation of the tobacco control laws. Therefore, SHS exposure at home might have an important public health impact.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, many studies showed a higher toxicity for cigarette smoke compared with ambient PM sources such as dust and traffic . To improve indoor air quality for people especially for vulnerable groups, SHS is still an important pollutant from a public health perspective …”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66] To improve indoor air quality for people especially for vulnerable groups, 67 SHS is still an important pollutant from a public health perspective. 1,20 Peak analysis developed in this study allows us to quantify the contribution of PM 2.5 from SHS exposure from specific locations and time periods. Data from this study and studies using this approach can inform and shape health policy regulating SHS, especially for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study was found that smoking in the whole house was a significant factor of positive urinary cotinine in pregnant nonsmokers [1]. Pollution from secondhand smoke (SHS) smoke from burning cigarettes inhaled by nonsmokers especially in the form of gases can be disposed of if there is air ventilation, but can settle on the surface for a certain time on floors, walls, chairs, fabrics, clothing, carpets, furniture that this has the potential as thirdhand smoke [2][3] [4][5] [6].…”
Section: Introductionmentioning
confidence: 99%